Change in the capability of reactive oxygen species production by neutrophils following weight reduction in female judoists - Yaegaki, M.; Umeda, T.; Takahashi, I.; Matsuzaka, M.; Sugawara, N.; Shimaya, S.; Tanabe, M.; Kojima, A.; Mochida, N.; Yamamoto, Y.; Nakaji, S. (British Journal of Sports Medicine, 2007)
Objective: Athletes undergoing weight reduction are recognised as being more prone to infection. Few studies exist for athletes on the weight reduction-mediated changes in neutrophil function and related activities such as reactive oxygen species (ROS) production capability, phagocytic activity (PA) and serum opsonic activity (SOA).